The tolerance of Freshwater Catfish Clarias Macrocephalus Gunter to different concentrations of insecticides commonly used in ricefields at Leganes, Iloilo - Griño, Eliseo
The object of this study was to determine the tolerance limit of juvenile freshwater catfish Clarias nacrocephalus Gunther to different concentrations of insecticides commonly used in rice fields at Leganes, Iloilo. The availability of an adequate supply of healthy fish of desirable uniform size and its adaptability to the laboratory conditions of temperature, feeding, and handling governed the selection of this species. Three experiments were conducted (one for each of three common insecticides). For each experiment four serial dilutions of the insecticides were tested on an equal number of fish placed in ten plastic bags of 60-liter capacity. One set of the experimental plastic bags (one original and one replicate) served as control. Free dissolved oxygen, temperature, and pH were determined before the start and after each trial. Fish mortality was recorded within 12, 24, and 48-hour periods. Dead fish were moved immediately from the plastic bag in order to prevent the factor of putrefaction from contaminating the experiment. The derivation of the median tolerance limit (TLm) by interpolation involves the plotting of the experimental data on semilogarithmic coordinate paper with test concentration laid off on the logarithmic scale and survival percentages on the arithmetic scale. It was found out that granule formulation produced a delayed effect as compared to the rapid and acute effect of liquid formulation, when the fish was exposed to the formulation for the same length of time. No mortality was recorded when fish was exposed at 0.120 p.p.m. ; and at 0.045 p.p.m. Fish kill was recorded at 18-hour exposure to toxicant. A stage may have been reached when further increase in the concentration will materially shorten the survival time. This investigation has pointed to the need for similar studies in other categories such as insecticides being influenced by soil type, land cover, rainfall intensity and frequency, organic content, and water turbidity. Further study is quite necessary to determine more precisely the extent of effectiveness and degradation of the insecticide could be obtained for further evaluation.
Seminar Paper (Master of Arts in teaching Biology). -- Diliman, Q.C. : UP College of Education, March 1976.